The role of media in developing the economic return of sports events - Dahroug Mohamed, Fawzy (sports creativity, 2025)
This research aims to identify the role of the media in developing the economic return of sports events and the researcher used the descriptive approach. The research community consists of editors of sports newspapers and preparers and providers of sports programs in Egypt and Algeria. The researcher has chosen a random sample of editors of sports newspapers and preparers and providers of sports programs, and some heads And members of Arab sports federations, and some leaders of the ministries of information at various administrative levels in Egypt and Algeria. The total sample reached (128) individuals, and the researcher used (30) individuals as a survey sample for data collection tools: The researcher designed the questionnaire As a tool to collect data to determine the appropriate themes and phrases, it has been identified number (4) axes and was one of the most important results Guying towards taking into account the factors of international security and safety for media professionals and guidance towards obtaining appropriate sports legislation